An overview on heterogeneous Fenton and photoFenton reactions using zerovalent iron materials - Litter, Marta Irene (2017)
The basic and applied aspects of Fenton and Fenton-like processes for removal of pollutants using zerovalent iron materials, including nanoparticles, are reviewed in this article. Only those examples including the use of the iron materials together with hydrogen peroxide addition are included. The mechanistic aspects of homogeneous and heterogeneous Fenton processes, still under discussion, are displayed. The use of biogenic generated iron nanoparticles for removal of pollutants is discussed due to their novelty and economy of synthesis.